Isolation and characterization of the active glycoside IN Nerium oleander L. (Adelfa) leaves extract as a potential pesticide - May Theresa B. Lao. 4 0 16; 5 (2003)
u
Undergraduate Thesis: (Bachelor of Science in Chemistry) - Pamantasan ng Lungsod ng Maynila, 2003.
Keywords: 2 -- 0; 6; 20; 20; 2